Genes required for developmental signalling in Myxococcus xanthus: three asg loci. - Kuspa, A (1989)
asg-carrying strains of Myxococcus xanthus arose in a selection for mutants defective in cell-cell signalling during fruiting body development. All 15 asg mutations examined were found to lie in one of three genetic loci, asgA, asgB, or asgC. The loci were defined by linkage to different insertions of transposon Tn5 and molecular cloning of asgA. asg mutants of all three types were deficient in the aggregation of cells into mounds of the sort that normally give rise to fruiting bodies. asg mutants were also deficient in spore formation; sporulation is normally one of the last steps in fruiting body development. Consistent with a requirement for cell-to-cell signalling, at 1 to 2 h asg+-carrying cells release a material called A-factor that can rescue development of asg mutants. asgA, asgB, and asgC mutants released 5% or less of the asg+ level of A-factor, as measured by bioassay. The experimental results are consistent with the hypothesis that a deficiency in A-factor production or release is the primary developmental defect in asg mutants and that aggregation and sporulation depend on A-factor. asg mutations at all three loci also changed the color and morphology of growing colonies, and failure to release A-factor may itself arise from a defect in growing cells.